Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Ilmu Pengetahuan Alam (Ipa) Siswa Kelas V Di UPTD SD Negeri 125549 Pematang Siantar - Netti Yuniarta Simatupang; Aprido B Simamora; Selamat Triadil Saragih (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the effect of the Talking Stick learning model on the learning outcomes of Natural Sciences (Science) for Class V students at UPTD SD Negeri 125549 Pematang Siantar. The design of this research is Pre-Experimental with the form of One-Group Pretest-Posttest Design. The population of this study was all class V UPTD students at SD Negeri 125549 Pematang Siantar, totaling 24 students. There are two hypotheses in this research, (1) there is an influence of the Talking Stick learning model on the learning outcomes of class V students in Theme 3 "Healthy Food" Subtheme 2 "Healthy Food for the Body" at UPTD SD Negeri 125549 Pematang Siantar (Ha) and (2 ) there is no influence of the Talking Stick learning model on the learning outcomes of class V students in Theme 3 "Healthy Food" Subtheme 2 "Healthy Food for the Body" at UPTD SD Negeri 125549 (H0). Data collection was carried out by giving pretest and posttest questions. Based on the results of the instrument test using the N-Gain test, a value of 0.77 was obtained, where in the Gain Interpretation Table the Normalized Value Score is 0.77, which is between the Ngain value <0.7 with high criteria. Based on the results of the normality test using Lilliefors, it was obtained that Lcount < Ltable (0.1137 < 0.1766), it can be concluded that the data obtained was normally distributed. So it can be concluded that there is an influence of the Talking Stick learning model on Natural Sciences (IPA) learning outcomes at UPTD SD Negeri 125549 Pematang Siantar. This means Ha is accepted and H0 is rejected